A Primary Telangiectatic Mandibular Osteosarcoma With Germ-Line Malignancy-Associated DNA Damage Repair Gene Polymorphisms: A Case Report - Muhammad Tahir; Eric X. Wei; Carlina Madelaire; Alice S. Yu; Guillermo A. Herrera; Rodney E. Shackelford (Case Reports in Oncological Medicine)
Primary mandibular telangiectatic osteosarcomas are very rare lesions, with only nine cases reported. Histologically, these lesions show multiple cystic blood-filled cavities traversed by neoplastic bone in septa lined by high-grade malignant cells. Here, we report an 81-year-old woman who presented with a mandibular mass, which was surgically resected and analyzed by histologic examination and whole exome DNA sequencing. A diagnosis of telangiectatic osteosarcoma was given. Comparative sequencing data analysis of paired benign and tumor DNA revealed 1577 variants unique to the tumor DNA, which clustered into several gene families, including those regulating DNA repair and apoptosis. Comparison of benign and tumor DNA revealed many shared gene polymorphisms associated with an increased cancer risk. These included polymorphisms in the ATM, p53, BRCA1, and BRCA2 and many other genes. Interestingly, the patient’s family history showed an unusually high cancer incidence, likely related to these cancer risk–associated polymorphisms. To our knowledge, this is the first-time sequencing applied to a mandibular telangiectatic osteosarcoma. Our findings may shed light on the molecular origins of these rare tumors and how they may relate to other tumors in related kindreds.